The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/03611981211010795
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle Dimensions Based Passenger Car Classification using Fuzzy and Non-Fuzzy Clustering Methods

Abstract: There has been globally continuous growth in passenger car sizes and types over the past few decades. To assess the development of vehicular specifications in this context and to evaluate changes in powertrain technologies depending on surrounding frame conditions, such as charging stations and vehicle taxation policy, we need a detailed understanding of the vehicle fleet composition. This paper aims therefore to introduce a novel mathematical approach to segment passenger vehicles based on dimensions features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Since the division of vehicles into segments by experts is not standardized and therefore not always uniform, and some vehicle models have recently positioned themselves as "crossovers" between established vehicle categories [7][8], it has become increasingly difficult and inaccurate to segment the vehicle population using conventional classification methods. Using mathematical approaches, vehicles can be uniformly divided into segments based on similarity features.…”
Section: Introductionmentioning
confidence: 99%
“…Since the division of vehicles into segments by experts is not standardized and therefore not always uniform, and some vehicle models have recently positioned themselves as "crossovers" between established vehicle categories [7][8], it has become increasingly difficult and inaccurate to segment the vehicle population using conventional classification methods. Using mathematical approaches, vehicles can be uniformly divided into segments based on similarity features.…”
Section: Introductionmentioning
confidence: 99%
“…The compilation of chosen attributes is detailed in Table 2. The selection of these features was informed by their significance as established in prior research 5,32,35 and based on the statistical evaluations presented in Additional Information 1. The selected attributes are the Maximum number of passengers, Power-to-mass ratio and Maximum cargo mass.…”
Section: Methodsmentioning
confidence: 99%
“…Some of them 6,[27][28][29] have investigated various schemes using statistical and exploratory data analysis, aiming to describe typical characteristics of each segment. However, due to the complexity of the classification problem, most of these studies 5,[30][31][32][33][34] have tackled the classification and dimensionality reduction task with advanced Machine Learning (ML) algorithms and principal component analysis techniques, respectively. These studies have demonstrated that ML techniques can successfully address the complex problem of cars classification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A typical data clustering process starts with a group of information items and splits them into k clusters using Euclidean distance and other similarity distance metrics. Partition-based clusters could satisfy a few of following requirements: i) Each cluster should have at least one data item and ii) In non-fuzzy clustering algorithms, each object must only be present in one cluster [9].…”
Section: Introductionmentioning
confidence: 99%